SPECTRAL CHARACTERIZATION AND EFFICACY OF BIOGENIC SYNTHESIZED SILVER NANOPARTICLES USING SECONDARY METABOLITE OF PSEUDOMONAS AERUGINOSA ON SELECTED PATHOGENS (FUDMA JOURNAL OF SCIENCES, 2025)
Bacteria resistance to conventional antibiotics has made researchers look for other possible alternatives which include the use of nanoparticles, plant extracts, production of bacteriocin, organic acids etc. This study is focused on biosynthesizing AgNPs using secondary metabolite of Pseudomonas aeruginosa, characterize and evaluate its effectiveness against selected bacteria pathogens. FTIR, UV-visible spectroscopy, TEM analyses were used to characterize, agar disk diffusion method was employed for antibacterial sssay.  Bacterial pathogens used include Escherichia coli, Serratia liquefaciens, Bacillus subtilis, Pseudomonas aeruginosa, Citrobacter freundii, Staphylococcus aureus, Klebsiella pneumoniae, Enterobacter cloacae, Yersinia enterica and K. oxytoca. Colour change to dark brown indicates AgNPs synthesis. UV-vis spectrophotometer revealed peak absorbance 2.082 A at 410 nm, FTIR analysis revealed highest peak at 3458.58. Synthesized AgNPs size obtained ranged between 10.02 nm and 1.47 nm. Antibacterial assay result showed that AgNPs was effective against seven pathogens with P. aeruginosa (21.7 mm) as the most susceptible. E. coli and K. oxytoca were the most resistant with susceptibility to one antibiotic each while E. coli showed little susceptibility to AgNPs. All isolates showed resistance to more than half of the antibiotics used hence making them multidrug-resistant strains. In this study, it was observed that AgNPs were as effective as the antibiotics used.
Keywords: Pathogens; Resistance; Secondary metabolite; Silver nanoparticles; Susceptible